Transformation of nitrogen and sulphur impurities during hydrothermal upgrading of low quality coals. (15th January 2016) - Wang, Zhihua; Li, Qian; Lin, Zhenmin; Whiddon, Ronald; Qiu, Kunzan; Kuang, Min; Cen, Kefa
Abstract: The influence of hydrothermal upgrading on the configuration of nitrogen and sulphur species in coal was investigated in this paper. Hydrothermal modification of three typical Chinese lignite was performed at 200 °C, 250 °C and 300 °C. It was found that hydrothermal modification reduced the moisture content of coal and therefore increased the heating value. X-ray photoelectron spectroscopy (XPS) was used to analyze the speciation of nitrogen and sulphur in coal samples before and after the hydrothermal modification. XPS peak fitting analysis was performed by using the XPSPEAK points-peak software. Results showed that the hydrothermal treatment destroyed micro-structures and altered the functional groups of nitrogen and sulphur in coals. Nitrogen, which originally detected as a pyrollic peak (N-5), was converted to pyridic (N-6) or quaternary nitrogen (N-Q) species after the hydrothermal upgrading. Quaternary nitrogen associated with polycyclic aromatic hydrocarbon was converted to N-6 while N-Q molecules located at the coal edge transformed to nitrogen oxides (N-X). Sulphoxides, sulphones and sulphides were converted to thiophenes; alternatively, sulphides transformed to pyrite. These changes could result in a decrease in SO2 emission. Furthermore, there may be the transformation form sulphoxide and sulphone to sulphonates. Organic sulphur, to some extent, transformed to inorganic sulphur during the hydrothermal process.